CTNI-29. INVESTIGATING SAFETY AND EFFICACY OF TTFIELDS PRIOR AND CONCOMITANT TO RADIOTHERAPY IN NEWLY DIAGNOSED GLIOBLASTOMA - FIRST RESULTS OF THE PRICOTTF PHASE I/II TRIAL. (14th November 2022) - Kebir, Sied; Lazaridis, Lazaros; Schmidt, Teresa; Oster, Christoph; Feldheim, Jonas; Pierscianek, Daniela; Proescholdt, Martin; Hau, Peter; Grosu, Anca-Ligia; Krex, Dietmar; Sure, Ulrich; Scheffler, Björn; et al.
Abstract: Background: A synergistic inhibiting effect on glioblastoma cell proliferation was reported for the combination of TTFields and radiotherapy. Based on these preclinical findings, we performed the phase I/II PriCoTTF trial in adult nGBM patients to investigate the safety and efficacy of TTFields therapy initiated prior and concomitant to radiochemotherapy. MATERIAL AND METHODS: In this phase I/II trial, TTFields therapy was initiated following surgery and continued throughout radiochemotherapy and adjuvant chemotherapy for a total of approximately 9 months. TTFields rechallenge was allowed at recurrence. Radiotherapy was conducted with arrays applied on the patients' scalp. Safety and tolerance are the study's primary endpoint, determined by a selection of pre-specified treatment-limiting toxicities (TLTs). RESULTS: A total of 33 patients have been enrolled. Patients' characteristics were mostly typical for glioblastoma, except for a rather low fraction of patients with gross total resection (GTR, 22.5%). The distribution of adverse events of ≥ common toxicity criteria (CTC) grade 3 was comparable to that of established glioblastoma trials. Notably, skin toxicity of ≥ CTC grade 3 was uncommon (n = 2, 6%). No patient developed TLTs. Median TTFields treatment duration was 8.4 months. Overall survival data was not mature enough (event rate 48%) to allow for a definite conclusion Notably, on multivariable Cox regression, the number of days with TTFields adherence > 23 hours was independently associated with overall survival (HR 0.96, 95% confidence interval 0.93 - 0.99, p = 0.008). CONCLUSION: The PriCoTTF trial met its primary endpoint indicating that combined TTFields and radiotherapy is safe and well tolerated. High-grade skin toxicity was quite uncommon and the patients with high TTFields adherence seem to perform particularly well. An extended follow-up is required to provide first estimates regarding putative efficacy. At that point in time, the reduced overall TTFields duration and fraction of patients with GTR need to be factored in.